Data analysis methods adopted under in situ global project in Nepal - Joshi, Bal K; Upadhyay, Madhusudan P; Bimb, Hari P; Gauchan, D; Baniya, BK (Nepal Agriculture Research Journal, 2010)
Synthesizing data analysis methods adopted under in situ global project in Nepal along with variables and nature of study could be guiding reference for researchers especially to those involved in on farm research. The review work was conducted with the objective to help in utilizing and managing in situ database system. The objectives of the experiment, the structure of the treatments and the experimental design used primarily determine the type of analysis. There were 60 papers of this project published in Nepal. All these papers are grouped under 8 thematic groups namely 1. Agroecosystem (3 papers), 2. Agromorphological and farmers’ perception (7 papers), 3. Crop population structure (5 papers), 4. Gender, policy and general (15 papers), 5. Isozyme and molecular (6 papers), 6. Seed systems and farmers’ networks (5 papers), 7. Social, cultural and economical (11 papers) and 8. Value addition (8 papers). All these papers were reviewed basically for data type, sample size, sampling methods, statistical methods and tools, varieties and purposes. Descriptive and inferential statistics along with multivariate methods were commonly used in on farm research. Experimental design, the most common in on station trial was least used. Study over space and time was not adopted. There were 5 kinds of data generated, 45 statistical tools adopted in eight different crop species. Among the 5 kinds of data under these eight subject areas, categorical type was highest followed by discrete numerical. Binary type was least in frequency. Most of the papers were related to rice followed by taro and finger millet. Cucumber and pigeon pea were studied least. Descriptive statistics along with Χ2, multivariate analysis and regression approaches would be appropriate tools. Similarly SPSS and MINITAB may be good software. The best one among a number of statistical tools should be selected and utmost care must be exercised while collecting data. Key words: Data analysis methods; on farm research; on station research; subject areas DOI: 10.3126/narj.v6i0.3371 Nepal Agriculture Research Journal Vol.6 2005 pp.98-108